Relationships Between Immune‐Inflammatory Features and Social Cognitive Impairments in Patients With Schizophrenia Spectrum Disorders: A Systematic Review - Alexandre Carpentier; Dimitrios Zampetas; Alexandre Durand; Mickael Naassila; Marie‐Cécile Bralet (Brain and Behavior)
ABSTRACT Introduction Patients with schizophrenia spectrum disorders (SSD), particularly patients with schizophrenia, have social cognitive impairments characterized by difficulties in emotion recognition, the ability to attribute mental states, explaining the causes of events, and identifying and utilizing social cues. These impairments appear from early life and are associated with poor functional and social prognosis. The origin of these impairments is not fully understood. The inflammatory hypothesis is one of the pathophysiological hypotheses of schizophrenia. Inflammatory marker abnormalities are also present in the early stages of schizophrenia and are associated with neuronal degeneration. Following our main hypothesis, the aim of this work was to conduct a review to explore the relationship between social cognition and inflammatory markers in SSD. Methods The review included original studies reporting measures of social cognition and plasma levels of inflammatory markers in patients with SSD using the Pubmed, PsycINFO, and Embase databases. The PRISMA methodology was followed. Results Eleven studies were selected and analyzed. They showed significant correlations between plasma cytokine levels and theory of mind and facial emotion recognition abilities. Conclusion The correlations do not seem to be specific to social cognitive impairments, but our results support the hypothesis of a link between pro‐ and anti‐inflammatory markers and cognition in SSD. In the future, other studies should be conducted to clarify this link from a diagnostic and therapeutic perspective: identification of inflammatory trait factors and patient subgroups and personalized anti‐inflammatory therapies.